Efektivitas Perasan Daun Keji Beling (Sericocalyx crispus Linn) Dalam Menghambat Pertumbuhan Staphylococcus aureus - Dita Artanti (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2017)
Indonesia with the title gemah ripah loh jinawi is never separated from the wealth of its natural resources, especially on the type of flora. Indonesia is rich in the types of medicinal plants one of which is a Keji beling plant. The Keji beling plants by the community are used as anti diabetic, diuretic, antisipilis, antioxidant, antimicrobial, and laksatif. A research has been conducted to determine the effectiveness of the vermicelli leaves (Sericocalyx crispus linn) in inhibiting the growth of Staphylococcus aureus. This study was experimental laboratory consisting of 24 samples with 6 treatments with 4 replications. The concentration of the vermicelli leaves is 0%, 10%, 25%, 50%, 75%, and 100%. The method used in this research is dilution method. Data were analyzed by ANOVA analysis at 5% error rate (α = 0,05). The follow-up test uses Tukey's Honest Significant Difference (Tukey's HSD) test. The results showed that the vermicelli leaves are effective in inhibiting the growth of Staphylococcus aureus. The concentration of the best Keji beling leaves that can inhibit the growth of S. aureus is at 100% concentration because only 19 colonies grow. While the minimum inhibitory power is obtained at a concentration of 75%. Key word :  Keji beling leaves, Staphylococcus aureus